Coupling between surface plasmon resonance and Sm3+ ions induced enhancement of luminescence properties in fluoro-tellurite glasses - Mechergui, Imen; Fares, Hssen [UNESP]; Mohamed, Shaimaa A.; Nalin, Marcelo [UNESP]; Elhouichet, Habib (Elsevier, 2017)
Fluoro-tellurite glasses co-activated with Samarium (Sm3+) ions and silver nanoparticles (Ag NPs) were prepared using melt quenching technique. The nucleation and growth of Ag NPs were controlled by thermal annealing process. X-ray diffraction (XRD), transmission electron microscopy (TEM), differential scanning calorimetry (DSC), UV–vis–NIR absorption spectroscopy, photoluminescence (PL) and PL lifetime spectroscopy were used to examine the annealing time dependence of the structural and luminescent properties. The amorphous nature of glasses has been confirmed by XRD spectra. The transmission electron microscopy images show the presence of silver NPs having an average diameter in the range of 20–40 nm. Selected area electron diffraction pattern (SAED), as well as EDX analysis spectrum confirm the presence of Ag NPs. Based on the absorption results, the intensity parameters Ωt (t=2, 4, 6), the radiative transition probability (AT), fluorescence branching ratio (βJJ’) and radiative lifetimes (τr) of Sm3+ ions were calculated using Judd-Ofelt theory. The results suggest that Sm3+ ions have been incorporated into Ag NPs, which intensified the electromagnetic field around Sm3+ ions. The luminescence properties of Sm3+ doped glasses were investigated. It was found that the presence of silver NPs nucleated and growth during the annealing process, improves the photoluminescence (PL) intensity and the PL lifetime relative to the transition from the 4G5/2 state to 6H5/2, 6H7/2, 6H9/2 and 6H11/2 states. Maximum enhancement is observed for the sample heat treated for 8 h. Such enhancement is mainly attributed to the local electric field created by the SPR of Ag NPs. whereas; the quenching is due to the energy transfer from Sm3+ ions to the silver nanoparticles as well as to the non-plasmonic, molecule likes Ag-particles (ML-Ag). The present results indicate that the glass heat-treated for 8 h has good prospect for Laser emissions at 600 nm.
Keywords: Fluoro-tellurite glasses; J-O theory; Photoluminescence enhancement; Silver nanoparticles; Surface plasmon resonance